Knowledge of God Almighty according to Sheikh Muhammad Al-Amin Al-Harari (may God have mercy on him - Ali Abdullah Salem; Idan H. Ibrahim (Islamic Sciences Journal, 2024)
ABSTRACT The first goal of all religion is to introduce Allah Almighty, as it is not right for a person to worship a Lord whom he does not truly know, and the Islamic sects differed regarding this knowledge. Some of them said: looking, and among them were those who said: the intention is to look, and among them were those who said: other than That, and Sheikh Al-Harari (may Allah have mercy on him) said: Knowledge of Allah cannot be attained except by Sharia law and that is through revelation, not by human machines of reason and otherwise, and that there is no life for souls except by knowledge of Allah Almighty.